Scandalous Behavior: Stone Barrington #36 - Woods, Stuart; Roberts, Tony, 1939- (New York, NY : Penguin Audio, 2016)
After several tiring adventures, Stone Barrington settles in the quiet British countryside, but he is soon troubled by a mystery that involves the complex relationships of the local gentry and a tireless adversary who is constantly raising the stakes.
Title from container.
Read by Tony Roberts.
Keywords: Barrington, Stone (Fictitious character) -- Fiction; Private investigators -- Fiction; Suspense fiction; Mystery fiction; Audiobooks